IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DAN PROFIL PELAJAR RAHMATAN LIL’ALAMIN DI SMA NEGERI 2 MUARA BADAK - Muhammad Firmansyah; Muhammad Nasir; Abu Bakar Idham Madani (Inspiratif Pendidikan, 2023)
This study aims to analyze and implement projects that support the strengthening of student profiles in aspects of Pancasila and Rahmatan Lil’alamin at SMA Negeri 2 Muara Badak. The projects involve Suara Demokrasi through the Election of Student Council Chair, Entrepreneurship with a focus on exploring the potential of the region through entrepreneurship, and Sustainable Lifestyle to realize plastic-free through the use of eco-bricks.